The Influence of Service Quality on Community Satisfaction at the Gowa Regency Public Service Mall - Andi Wahyu Gunawan; Ikhsan Hidayat (Journal Social Society, 2026)
The urgency of this research is to improve the detection and classification of IP spoofing and Man-in-the-Middle attacks on wireless networks by developing more effective machine learning-based security solutions. This study aims to examine the influence of service quality on community satisfaction at the Public Service Mall of Gowa Regency. The research adopts a quantitative approach using a survey method, with data collected from 97 respondents who had directly experienced public services at the facility. Service quality is measured using the SERVQUAL framework, which includes five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data analysis was conducted using multiple linear regression to test the relationship between service quality and community satisfaction. The results indicate that overall service quality has a positive and statistically significant effect on community satisfaction. Among the SERVQUAL dimensions, responsiveness and assurance emerge as the most influential factors, reflecting the importance of prompt service and staff competence in shaping user perceptions. Tangibles, reliability, and empathy also contribute positively, although challenges remain in terms of queue management, service efficiency during peak periods, and infrastructure capacity. These findings suggest that while the integrated service model has improved accessibility and convenience, continuous improvement in operational performance is still required to meet increasing public expectations. This study contributes to the public service management literature by extending the application of the SERVQUAL model in integrated service settings. Practically, the findings provide insights for policymakers to enhance service quality through infrastructure optimization, human resource development, and the adoption of digital service systems to improve efficiency and citizen satisfaction.